Transformation of Islamic Education Evaluation: : Building a Multidimensional Model for Character Development and Spiritual Skills in the Digital Age - Mokmin, Mohd Waffi Albaraq; Arifin, Syamsul; Mokmin Bin Basri (Tahta Media Group, 2025)
This study aims to develop a comprehensive evaluation model for Islamic education that integrates cognitive, affective, and spiritual dimensions while incorporating technology-assisted assessment methods. Utilising a mixed-methods approach combining qualitative literature analysis and quantitative instrument development (following the ADDIE model), the research identifies significant gaps in current evaluation practices, particularly the overemphasis on cognitive measurement and inadequate attention to character development. Findings reveal that while traditional evaluation methods dominate (with only 30% of Islamic schools adopting technology-based assessment), pilot implementations of the proposed multidimensional model demonstrate 42% improvement in character outcomes and 35% increased assessment efficiency. The study highlights three key innovations: (1) a three-domain evaluation framework aligned with Islamic educational objectives, (2) digital assessment tools preserving sharia principles, and (3) practical training modules for educator capacity building. Results further indicate that technology integration significantly reduces evaluation time (by approximately 60%) while improving accuracy in spiritual development tracking. The research contributes to educational reform by offering standardised instruments for holistic student assessment and evidence-based policy recommendations to align national education systems with Islamic values, addressing historical limitations in Islamic educational evaluation since the 12th century.